How ball games experts legitimate ball games knowledge within Swedish physical education teacher education - Mustell, J.; Geidne, S.; Barker, D. (Physical education and sport pedagogy, 2024)
Various forms and types of knowledge have enjoyed legitimacy in physical education (PE) since sports techniques became the orienting idea for PE in economically advanced countries in the mid-twentieth century. The forms and types of knowledge granted legitimacy at any one moment are dependent on a range of socio-discursive factors. In this paper, we consider ball games knowledge within the Swedish PE teacher education context in the 2020s. The specific aim of the paper is to generate insights into how ball games experts within PE teacher education define legitimate ball games knowledge. Our proposition is that by examining the ways these experts define ball games knowledge, physical education teacher educators may develop more nuanced understandings of how and why knowledge comes to be seen as legitimate. In order to conceptualize experts' knowledge of ball games, Shulman's concepts of content knowledge (CK) and pedagogical content knowledge (PCK) were employed. Semi-structured interviews were conducted with two teacher educators who specialized in ball games education from three different PETE institutions in Sweden (n = 6). The interviews focused on the PETE educators' understandings of ball games and how they prepared preservice teachers to teach ball games. The PETE educators defined ball games CK as: (1) understanding of games as a cultural phenomenon, (2) tactical understanding of games, and (3) embodied understanding of how to play ball games. The PETE educators defined ball games PCK as: (1) using ball games to meet different curricular goals, (2) focusing on tactical understanding with a small number of concepts, (3) adapting teaching so that all pupils are included, and (4) managing competition. Four issues related to the legitimacy of this knowledge are raised. The issues concern the ways in which: (1) a complementary sport discourse is permeated by educational discourse to achieve legitimacy; (2) CK and PCK are designed to achieve legitimacy with different stakeholders; (3) public health discourse is not used to develop legitimacy for ball games knowledge, and (4) historical factors continue to affect experts' understandings of ball games. The central conclusion drawn from the investigation is that ball games experts engage in a complex process of discursive negotiation when defining the knowledge with which they work.